The Impact of Parental Migration on the Emotional Development of Left Behind Children in Rural Pakistan - Muhammad Adil; Sabeela Naz; Komal Waheed; Zaib Samraz; Saria Rafiq; Nusrat Jabeen (Research Journal of Psychology, 2025)
Background: Parental migration has become a widespread phenomenon globally, with many children left behind in their home countries. While migration often improves the financial situation of families, it can adversely affect the emotional and behavioral development of children. Previous studies have indicated that children left behind by migrant parents face increased challenges in their social and emotional well-being, but research focusing on rural areas, particularly in Pakistan, is limited. Aim: The aim of this study was to investigate the impact of parental migration on the emotional development of left-behind children in rural Pakistan, with a focus on emotional stability, social interaction, behavioral adjustment, and academic performance. Method: This study utilized a cross-sectional design and surveyed 300 children aged 11-19 from Lahore, Karachi, Islamabad, and Peshawar. Participants were divided into two groups: left-behind children (n=150) and non-left-behind children (n=150). The Parental Migration Questionnaire (PMQ) and the Behavior Problems Index (BPI) were used to assess the children's emotional and behavioral outcomes. Statistical analyses, including t-tests and correlation analysis, were performed to determine the significance of the results. Results: The findings revealed that left-behind children exhibited significantly poorer emotional stability, social interaction, behavioral adjustment, and academic performance compared to their non-left-behind counterparts (p<0.01). A strong positive correlation was found between parental migration and behavioral problems (r = 0.91, p < 0.01). Conclusion: The study concluded that parental migration has a detrimental effect on the emotional development of left-behind children, highlighting the need for targeted interventions and support for these children to mitigate the negative outcomes associated with parental absence.